Rhynchophylline Attenuates Senescence of Endothelial Progenitor Cells by Enhancing Autophagy - Lin, Lin; Zhang, Lei; Li, Xin-tong; Ji, Jing-kang; Chen, Xiao-qing; Li, Yun-lun; Li, Chao (Frontiers in Pharmacology, 2020)
The increase of blood pressure accelerates endothelial progenitor cells (EPCs) senescence, hence a significant reduction in the number of EPCs is common in patients with hypertension. Autophagy is a defense and stress regulation mechanism to assist cell homeostasis and organelle renewal. A growing number of studies have found that autophagy has a positive role in repairing vascular injury, but the potential mechanism between autophagy and senescence of EPCs induced by hypertension has rarely been studied. Therefore, in this study, we aim to explore the relationship between senescence and autophagy, and investigate the protective effect of rhynchophylline (Rhy) on EPCs. In angiotensin Ⅱ (Ang Ⅱ)-treated EPCs, enhancing autophagy through rapamycin mitigated Ang Ⅱ-induced cell senescence, on the contrary, 3-methyladenine aggravated the senescence by weakening autophagy. Similarly, Rhy attenuated senescence and improved cellular function by rescuing the impaired autophagy in Ang Ⅱ-treated EPCs. Furthermore, we found that Rhy promoted autophagy by activating AMP-activated protein kinase (AMPK) signaling pathway. Our results show that enhanced autophagy attenuates EPCs senescence and Rhy rescues autophagy impairment to protect EPCs against Ang Ⅱ injury.